DEVELOPMENT OF PROJECT STORYNOMICS TOURISM BASED ON A DIGITAL PLATFORM FRIENDLY FOR DISABLED TOURISTS IN MALANG CITY - Widyatmoko, Tiksno (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
This research aims to develop a digital platform for Project Storynomics Tourism that is friendly to disabled tourists in the city of Malang. The development research model uses the ADDIE method which contains five stages. The Storynomics Tourism project was developed to contain promotions that use a story approach about history and the location behind a tourist attraction along with sign language videos that are displayed on inclusivethoughts.id on Instagram. The results of the data in the form of a questionnaire obtained from the validation process of experts, trials on users, and the validity of the findings with a triangulator were analyzed using descriptive quantitative and descriptive qualitative techniques. the community of observers for persons with disabilities in the city of Malang, Omah Gembira, is the source of data from development research as well as the Head of the Department of Youth, Sports and Tourism in Malang City. The development research results stated that the Storynomics Tourism Project was very good to be developed and used.Keywords: development; disability platforms; tourist; inclusive; Project Storynomics Tourism.